ANALISIS LITERASI BACA TULIS SISWA DALAM MATA PELAJARAN BAHASA INDONESIA KELAS IV DI SD NEGERI 08 PAYARAMAN - Hastuti, Nely; Hetilaniar, Hetilaniar; Selegi, Susanti Faipri (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to analyze fourth-grade students’ literacy skills in reading and writing in the Indonesian language subject at SD Negeri 08 Payaraman. The research employed a qualitative approach, with data collected through classroom observations and structured interviews with the principal, the fourth-grade teacher, and several students. The results showed that literacy activities have been routinely implemented and integrated into the learning process. Most students demonstrated adequate reading comprehension and structured writing skills. The school provides supporting facilities such as a library and reading corners, although their utilization still needs improvement. The main challenges faced by students include limited vocabulary, low reading interest, and difficulty understanding implicit meanings in texts. In addition, the family environment plays an important role in shaping students’ reading and writing habits at home. In conclusion, fourth-grade students’ literacy skills are generally at a satisfactory level. However, more adaptive and collaborative learning strategies, along with active parental involvement, are needed to address students’ difficulties. Strengthening literacy environments at school and home is recommended to enhance students’ overall literacy skills.